PENGARUH KOMPENSASI, MOTIVASI DAN KEPUASAN KERJA TERHADAP KELUAR MASUK PEGAWAI (LABOUR TURNOVER) PADA PT. ASURANSI ABC SURABAYA - J.F.X Susanto Soekiman (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2007)
The research oberves the effects of compensation, motivation, and woriking satisfaction toward the labour turnover in PT Asuransi ABC Surabaya.The results are known that (1) the coeficien correlation value (R) from linier regression is 0.882, meaning correlation between dependent & independent variables is trong at 88,2 %; (2) the value of coeficien determination square (R2) is 0.778, meaning 77.8 % of labour turnover variations are influenced by three variables i.e. : compensation variable (X1), motivation (X2), and working satisfaction (X3); (3) the rest value 22.2 % is known that labour turnover is PT Asuransi ABC Surabaya is influenced by ather independent variable. So, there are simultaneous and partial effects from dependent variable toward independent variable.